1998
DOI: 10.1152/ajpregu.1998.275.1.r308
|View full text |Cite
|
Sign up to set email alerts
|

Increased physical activity and the growth hormone-IGF-I axis in adolescent males

Abstract: Insulin-like growth factor-I (IGF-I) is associated with muscle hypertrophy, and circulating IGF-I levels are correlated with fitness. To test the hypothesis that IGF-I increases with increased physical activity in adolescent males, 38 subjects (16 ± 0.7 yr old) were randomized to control ( n = 18) or increased physical activity groups for 5 wk. Before and after the intervention, we measured thigh muscle volume using magnetic resonance imaging and serum levels of mean growth hormone (GH) by overnight multiple s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
87
4
23

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(125 citation statements)
references
References 44 publications
11
87
4
23
Order By: Relevance
“…Exercise training is linked to anabolic function through this axis, as previous cross-sectional studies from this and other groups have demonstrated that GH pulsatility and circulating IGF-I are higher in fitter adolescents and adults (2)(3)(4)(5). In contrast, we have consistently demonstrated a decrease in circulating elements of the GH-IGF-I axis in postpubertal males and females and in prepubertal girls in response to aerobic exercise (6,7). This was surprising for two reasons: first, because the training regimen led to significant increases in muscle mass and fitness without weight loss; and secondly, because IGF-I is known to be correlated with fitness in adults and adolescents, indicating a training-associated enhancement of anabolic activity (3)(4)(5).…”
supporting
confidence: 69%
“…Exercise training is linked to anabolic function through this axis, as previous cross-sectional studies from this and other groups have demonstrated that GH pulsatility and circulating IGF-I are higher in fitter adolescents and adults (2)(3)(4)(5). In contrast, we have consistently demonstrated a decrease in circulating elements of the GH-IGF-I axis in postpubertal males and females and in prepubertal girls in response to aerobic exercise (6,7). This was surprising for two reasons: first, because the training regimen led to significant increases in muscle mass and fitness without weight loss; and secondly, because IGF-I is known to be correlated with fitness in adults and adolescents, indicating a training-associated enhancement of anabolic activity (3)(4)(5).…”
supporting
confidence: 69%
“…Several authors have described an increase in plasma IGF-I after endurance training (Poehlman et al 1994;Koziris et al 1999), but others have reported an opposite effect (Eliakim et al 1996(Eliakim et al , 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Possible direct actions of physical activity include effects on plasma levels of insulin and insulin-like growth factors (IGF). A sedentary life might lead to higher levels of these hormones [11][12][13] that both could contribute to the growth, proliferation or metabolism of renal cell cancer. 14 Epidemiological studies indicate that patients with diabetes, which is associated with higher plasma insulin levels, have an increased risk of renal cell cancer.…”
Section: Discussionmentioning
confidence: 99%